HSP90B1 regulates autophagy via PI3K/AKT/mTOR signaling, mediating HNSC biological behaviors - Li,Chao; Lin,Xiaoyu; Su,Jiping (PeerJ, 2024)
Background Autophagy, a crucial cellular mechanism, facilitates the degradation and removal of misfolded proteins and impaired organelles. Recent research has increasingly highlighted the intimate connection between autophagy and heat shock proteins (HSPs) in the context of tumor development. However, the specific role and underlying mechanisms of heat shock protein 90 beta family member 1 (HSP90B1) in modulating autophagy within head and neck squamous cell carcinoma (HNSCC) remain elusive. Methods Quantitative real-time PCR (qRT-PCR), Western blot (WB), immunohistochemistry (IHC) were used to detect the expression in HNSC cell lines and tissues. The relationship between HSP90B1 and clinicopathologic features was explored based on TCGA (The Cancer Genome Atlas) data and IHC results. The biological functions of HSP90B1 were analyzed through in vitro and in vivo models to evaluate proliferation, migration, invasion, and autophagy. The mechanisms of HSP90B1 were studied using bioinformatics and WB. Results HSP90B1 was upregulated in HNSC cells and tissues. High HSP90B1 levels were associated with T-stage, M-stage, clinical stage, and poor prognosis in HNSC patients. Functionally, HSP90B1 promotes HNSC cell proliferation, migration, invasion and inhibits apoptosis. We discovered that HSP90B1 obstructs autophagy and advances HNSC progression through the PI3K/Akt/mTOR pathway. Conclusion Our study demonstrates that HSP90B1 is highly expressed in HNSC. Furthermore, HSP90B1 may regulate autophagy through the PI3K/Akt/mTOR pathway, mediating HNSC cell biological behaviors. These provide new insights into potential biomarkers and targets for HNSC therapy.
Keywords: HSP90B1; HNSC; Autophagy; PI3K/AKT/mTOR signaling; Biological behavior